Grundtvigs udfordring til moderne theologi - Prenter, Regin (Grundtvig-Studier, 1973)
Grundtvigs challenge to modern theology By Regin Prenter In the first part of his paper Regin Prenter is concerned with presenting a simplified picture of modern theology, in order subsequently to examine the nature of Grundtvig’s challenge. He explains that he will confine himself firstly, to discussing modern protestant theology on the grounds that Grundtvig himself was a Lutheran, secondly, to treating systematic theology in the widest sense of the term, and thirdly, to pointing out prevalent tendencies in present-day systematic theology. The theological revolution for which Karl Barth was responsible between the First and Second World Wars brought about an increasing interest not only in biblical theology, but also in the study of the great Christian thinkers, the Church Fathers, the medieval scholastics and, above all, the reformers of the sixteenth century, who exerted a strong influence on the thought of these neoorthodox theologians, as they came to be called in the U.S.A. Today, Regin Prenter says, the younger generation of theologians, almost without exception, react somewhat violently against this theological renewal. Not that they would dream of returning to the essentially middle-class Liberal Theology of the turn of the century, despite their approval of its critical attitude towards the Classical Christian heritage, since the vast majority of them – disregarding the fundamentalists - are socialists and extremely critical of the "established" capitalist society of the West. "The World” is the focal-point of interest for theologians today. The main theological question is no longer, as it was between the Wars, "What do the Holy Scriptures say, or, What does the Church say, with regard to a given point?” but, "What can or should the Church, or Christians, do to change the world, in order to make it a better place to live in for the hungry and oppressed, who still constitute the greater part of mankind.” Under the influence of neo-marxist thinkers such as Ernest Bloch, political action is, to an increasing degree, becoming the criterion for theological truth, e.g. in Jürgen Moltmann’s Revolution theology. This does not mean that the theologians in question dissociate themselves from the "theology of Revelation” as such, some of them, indeed, for instance Jürgen Moltmann, being disciples of Barth and interested in a "theology of the Word”. But they are convinced that not all truth, including the truth of God’s Revelation, is apprehended as such, unless it is translated into action, i.e. political action. Biblical eschatology and the neo-marxist philosophy of hope merge into each other in Moltmann’s Theology of Hope. The Christian hope in the eschatological salvation of the whole universe is reduced to sentimental nonsense if it does not lead to political action, aiming at transforming the world here and now, by making it more human. People do not truly hope for eternal salvation unless they work actively for the earthly salvation of their fellow-men. It is at this point that Regin Prenter asks whether there is in fact room for a living God, since the plans for the transformation of the world overshadow this question. He asks whether “God” is not a word that only contains reality within the context of a political programme, and whether the “theistic” conception of God is anything more than a creation of the religious imagination. Theism, the idea of a personal God, being inextricably bound up with the Established Church in established society, must surely be sacrificed first if the world is to be radically changed. He finds it quite understandable that extreme forms of "world theology” sometimes become "atheistic Christianity”, a "God-is-dead” theology, or a Christ-centred theology, in which the man Jesus does not reveal God, but replaces him (as in Dorothee Sölle’s theology). Regin Prenter admits that not all the theologians who fall into the above category would draw such radical conclusions. He is nevertheless convinced that it is the most extreme forms of secular theology, and not the countless attempts at compromise between political theology and the theology of Revelation that reveal the desperate situation in which politically-engaged young theologians find themselves today. The more radical the thinking in these directions, the more imperative it becomes to make a final choice between God and the world, between the Bible and marxism. Jesus’ words: "You cannot serve God and mammon,” can easily be paraphrased as: "You cannot love the suffering world and the God of the Church.” Prenter asserts that if theology is the attempt by Christians to clarify the role of the Christian, and if this implies being committed to the love of mankind which is manifested in Jesus’ dealings with men, as described in the Gospels, then a revision of their whole theology seems essential, in order that the faith and love claimed by God in the old theology may now be transferred to the people of the suffering world. He postulates that such a revision would involve the renunciation of belief in the transcendent God. Christianity would have to be interpreted as the principle of human love, as preached and exemplified by Jesus called the Christ, thus making it necessary to abandon all the traditional dogma, indeed, even the idea of a transcendent God. He asks whether such an antitheistic interpretation of the Gospel is the only form in which Christianity can survive, and goes on to say that it is to theologians to whom such questions are vital that Grundtvig is a challenge. Here Regin Prenter turns to Grundtvig himself. Despite the fact that he was not a Doctor of Theology and never became a professor, Grundtvig’s hymns, sermons, historical and mythological works are permeated with theology Yet measured by the usual theological yardstick, he was a decidedly secular writer, being a poet, historian, philosopher, educationalist and politician. He was no "systematist”, and never succeeded in keeping the various aspects of his manysided activity separate. Thus throughout his theology we find his secular engagement constantly present as a disturbing and stimulating element, while his theology both underlies and bounds his secular thought and activity. It is this peculiarity of Grundtvig that makes him a challenge to modern secular theology. While admitting that it is impossible to formularize Grundtvig’s theology, Prenter maintains that one can however point to some unmistakable guiding principles in his theological thought, which can - cautiously - be expressed in two famous quotations from his hymns: Only in the bath and at the table (i.e. in Baptism and the Eucharist) Do we hear God’s word, spoken to us. First a man and then a Christian, this is a fundamental. Prenter finds that there is a remarkable exclusiveness in this conception of the Church; "no salvation outside the Church" pales beside Grundtvig’s "only in the bath and at the table." Only when God’s people is assembled, only through the divine service and the institutions given by the Lord, does God speak to His people. Conversely, only when and where God speaks, at Baptism and the Eucharist, is God’s people present as a spiritual community. The Church, as Grundtvig understands it, is not the world, nor a part of the world, and neither is the world the Church, not even potentially. The Church is the people of God as a spiritual community, drawn from all nations and speaking all tongues. Grundtvig’s Church-centredness makes him a catholic theologian (in the early Church sense of the word), but not a Roman Catholic. Nevertheless he always considered himself a true Lutheran, since for him both the baptismal font and the Communion table are the places where God speaks to his people. And God himself has chosen where and how he will speak. Both ideas are essentially Lutheran. To the question of why Grundtvig binds God’s word to the Church Sacraments of Baptism and the Eucharist, Regin Prenter gives two answers. 1) The life-giving word of God is Jesus Christ himself. Grundtvig sees Baptism as the New Covenant between God and His people, God and fallen man, founded upon God’s Creation and redemptive work in and through His only-begotten Son. Therefore Baptism is performed in the name of the Trinity, in the name of the Father, Son and Holy Ghost. Only the Trinity can say what this name contains, and does so at the baptismal ceremony, in the Apostles’ Creed, understood as God’s own interpretation of His name in and through the history of the Creation and the Redemption, the events of which are summed up in the three articles of the Creed, the centre being the life, death and resurrection of Jesus Christ. The very first sentence takes us far outside the church walls, with the mentioning of the creation of heaven and earth and all that is therein. But it is in the churchbuilding, at the font, that God speaks the word that takes us out into the vast universe. That God’s own interpretation of the secret of His name is expressed in the form of a question (Do you renouce. . .? Do you believe...) is of great importance to Grundtvig (which is why, as long as Grundtvigians exist, there would be an uproar in the Danish People’s Church if any attempt were made to abolish the questions at Baptism). It means that life in this name, faith itself, is not a possibility or a choice open to man, but a gift of God; a gift in so complete a sense, that He even gives us the wording in which we accept His offer. In the Eucharist, God’s word to His people is bound up with the gifts of the Body and Blood of Jesus; it is a "declaration of love”whereby God establishes communion between Himself and all those who were baptized in the name of the Trinity, and who believe in and confess that name. 2) Man, created in God’s image, and to whom God speaks His life-giving word in Jesus Christ, is a wonderful mixture of spirit and flesh. The word that God speaks to mortal men in Jesus Christ is not an expression of timeless truths in human terms, but God’s own eternal truth, made man and therefore a historical word. By assuming the nature of a body (the water at Baptism and the bread and wine at the Eucharist) God’s life-giving word becomes an event, or rather, the event, the decisive event in the history of every human being. Baptism is the new birth into God’s kingdom, into life in His truth, and like every birth it is an unrepeatable event. The Eucharist is the event of God’s communion with man, that takes place here and now, at the Communion table, in a particular church on a particular Sunday. Grundtvig confronts the socialist engagement of modern theology with the orthodox Christian distinction between earthly and eternal salvation. All human beings are subject to death, as every single one of them has turned away from God their Creator. No revolution, no earthly "salvation now” in the shape of social justice and economic equality can give a human being eternal life and liberate him from death. The perfect human life, which man is created in God’s image to live on earth, is not possible unless death has been vanquished. But in Christ, mortal men are born again and raised up, in such a way that they live here and now in faith, hope and love as the people of God, man being born again to eternal life at Baptism and the reborn life being nourished by the Eucharist. This is man’s "Christian, spiritual and eternal life”. Man is created for eternal life, and even in the most just of all societies, even in the most perfect socialist state, he cannot attain eternal life without Christ and His people, without Baptism and the Eucharist. Grundtvig’s provocative question to modern, politically (socialist)-oriented theology is this: "Is not this theology, in the interests of the social revolution, sacrificing the Christian belief in God and in the eternal destiny of man?” Regin Prenter now tackles the second quotation: "First a man, and then a Christian”. He points out that Grundtvig does not say that man is not truly human until he has been born again to eternal life in Jesus Christ. It was precisely this misunderstanding, shared by medieval Catholicism and orthodox Lutheranism that, from 1825 onwards, he fought so passionately against. Every human being is, as a human being, God’s creation, and therefore truly man. If it were not so, God’s eternal Son could not have been made man and we could not have been saved from death to everlasting life, through being made participants in His perfect human life. The fact that man has fallen, that he is a sinner without the power or the right to forgive himself, that he is a mortal creature unable by himself to gain eternal life, does not mean that he has ceased to be God’s creation. Before Christ, outside the Church and the sacraments, we find genuine humanity, which is waiting for its liberation from sin and death, which is capable of being redeemed and raised to eternity in Jesus Christ and which also, in its fallen, unredeemed, earthly and mortal state is and remains true humanity, neither brutishness nor devilishness. "First a man and then a Christian” says that nobody can become a Christian, i.e. believe in God and his own eternal destiny in Christ, hear and trust in God’s life-giving word at Baptism and the Eucharist, devote himself to a life of faith, hope and love, without first being a man, God’s creation, created in His image. Grundtvig maintains that there is a way leading from true created humanity to eternal life in Jesus Christ. There is no way leading from the denial of our created humanity to salvation. Men can deny their own divinely created humanity, thereby closing the way to Christ. Grundtvig, the preacher of joyful Christianity, has never disputed the possibility of perdition. Prenter now turns to the question of language, as Grundtvig states clearly that humanity consists in the gift of speech. In the gift of speech man has, in his fallen state, preserved a sense of truth and a longing for life which is the essence of true humanity and, as such, the absolute prerequisite for man’s salvation from sin and death. In every human word there is an element of truth, love and life-giving power, corresponding, as Grundtvig shows in his theological treatise: “The Divine Trinity”, to the three divine names in the Trinity - life-giving power corresponding to the Holy Ghost, truth to the Son and love to the Father. This truth, love and life-giving power inherent in any human word, in so far as it is truly human, is not the divine truth, love and life-giving power inherent in God’s redeeming word in Jesus Christ - yet it comes from God, in and through every single living language, into the mind and body of man, making him truly human. Grundtvig is fully aware that this man is a sinner, but a human sinner, not an animal or a devil, and therefore able to hear and trust in the word that convinces him of his guilt and forgives him his sin. This man is also mortal, but again, he is able to hear and trust in the word that convinces him of his need of eternal life and which offers him eternal life. No man can speak such a word, but he is capable of hearing it when God speaks it, because he can himself speak words containing an element of truth, love and life. God will be able to speak to him in the language that he himself speaks. The language spoken by human beings is however always a particular language, different from other languages, a mother-tongue. A living universal language does not exist. The mere fact that a person is capable of using a foreign language in order to speak to the people of that nation does not make it his mother-tongue, even if he speaks it to perfection. Indeed, it is usually this very perfection that betrays the fact that it is not his mother-tongue. The language in which human truth, love and life-giving power can find their way from one man’s heart to another is the mother-tongue. It is, of course, possible to have human contact with those who do not speak our language and to worship with them in what is for us a foreign tongue, but only in so far as our mother-tongue is a spiritual power for us, through which truth, love and life pervade our souls and bodies, making us truly human. To realize one’s own true humanity, to become "truly man” is to develop one’s humanity in a spiritual fellowship, within a particular people, with a particular mother-tongue. This spiritual fellowship comes into being through the use of a living word in the mother-tongue, a word which reveals the spiritual power entrusted to this people by the Creator, and which itself brings about achievements that are the concrete manifestation of the spiritual forces, truth, love and life-giving power, of this people - the “spirit of the people”, as Grundtvig expresses it. "First man and then a Christian” means that the spiritual life of the individual people, manifested in its living use of the mother-tongue, is the soil in which the Christian community must be planted and grow if it is not to wither and die. If however, the individual or the people misuses the language, robbing it of its truth, love and life-giving power, then the individual or the people, will lose its created humanity, becoming inhuman, demoniac. Such a demoniac distortion of the language can happen in many ways, but is most frequently encountered in the political sphere, where cynical propaganda replaces the living word. And where humanity is thus corrupted, the Word of God and the Church of Christ and the spiritual life of faith, hope and love cannot survive. First a man and then a Christian therefore means that man’s free faith in God and in his Son Jesus Christ, his free love of God and His people, his free hope of his own redemption in Jesus Christ are conditioned by his recognition of his own true humanity in the life upon earth, before he meets God’s word in Jesus Christ, before the gospel of redemption is preached to him. Grundtvig’s orthodox and Church-centred Christianity is more genuinely secular, more concerned with the world than the greater part of modern secular theology. Prenter, in the final part of his paper, discusses the significance of these Grundtvigian ideas for the theologian, who, as a theologian, participates in the political struggle of our day. He should quite simply realize that in his political engagement he must not try to be Christian, but only human; as a theologian he cannot commit himself politically, but only as the human being that he also is. For all its would-be modernism and progressiveness, modern secular theology is essentially old-fashioned. The Christian politics of medieval theocratic society and the political Christianity of modern theology are twins. They both – although each in its own way - repudiate "First a man .. Grundtvig’s Christianity sanctions the engagement of the young thelogians in the struggle for a just and human society. Prenter suggests that had Grundtvig been alive today, he would almost certainly have viewed neo-marxist youth with sympathy. But he would have had a question to put to them: "Do you really know what true justice and humanity are? Do you not lack respect for true socialism and its secular basis, since you try to ‘improve’ it with Christianity and ‘theology’?” Grundtvig’s Christianity calls these theologians away from every form of theocracy, political Christianity and Christian politics, and from any attempt to make the Church political, and bids them devote their political enthusiasm and energy to making society more human. The Church does not, and cannot, fit into such an endeavour, which is why, in true socialism, the Church cannot be incorporated into the system, cannot even be of any help. Only a settled "socialist” dictatorship can "use” theologians - for propaganda. Hardly a desirable role. Is modern revolutionary socialism, of the type that attracts young theologians today, really human in its aims and means? Or is it in danger of becoming the victim of political demons? First a man! Theology and Christianity are not necessary in the struggle for political reform. There we need humanity – and whether it emanates from a Christian or a non-Christian, a theologian or a non-theologian is immaterial. Grundtvig then is a challenge to modern theology through his ability to distinguish between created and redeemed humanity, earthly and eternal life, people and Church, politics and faith - distinguishing between them in his thought, in order to unite them in his own existence as a Dane and a Christian. What has been honestly distinguished can be united in freedom. What has been dishonestly confused crushes the freedom of both Christianity and man.